Formula Optimization and Evaluation of Furosemide Powder Liquisolid Technique using Simplex Lattice Design - Dwi Retno Sari (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2021)
Liquisolid furosemide powder has been developed to overcome the problem of BCS (Biopharmaceutical Classification System) class IV which has low solubility and low permeability. The purpose of this research was to determine the optimum concentration of non-volatile solvent (PEG 400, glycerin, tween 80) and adsorbent (aerosil 200) in order to produce powder with the right proportions. The simplex lattice design analysis approach was used to determine the effect of concentration on the response of flow properties, angle of repose and compressibility of liquid furosemide powder. Determination of the optimum formula was carried out using Design Expert Version 11. The evaluation results showed that all formulas met the requirements, namely flow properties of 10 seconds, angle of repose ranging from 27-40° with good flow properties, but compressibility did not meet the requirements, the percentage yield was 23%. The analysis using the simplex lattice design approach produces a contour plot that provides positive and negative interactions for each response, so that the optimum formula for determining the optimum point for the equation of powder mixture properties using the simplex lattice design has a desirability value of 0.734 . The optimum formula is the formula that has the highest response. The calculation results obtained a formula containing a concentration of PEG 400 with a concentration of 1.95 grams, Glycerin 1.2 grams, Tween 80 2.7 grams and Aerosil 200 2.4 grams. So that the area can meet the response criteria (flow properties, angle of repose, and compressibility).